Effect of Balloon Guide Catheter Utilization on the Incidence of Sub-angiographic Peripheral Emboli on High-Resolution DWI After Thrombectomy: A Prospective Observational Study - Schönfeld, Michael H.; Kabiri, Reza; Kniep, Helge C.; Meyer, Lukas; McDonough, Rosalie; Sedlacik, Jan; Ernst, Marielle; Broocks, Gabriel; Faizy, Tobias; Schön, Gerhard; Cheng, Bastian; Thomalla, Götz; et al. (Frontiers in Neurology, 2020)
Background: Thrombus fragmentation causing distal emboli is a feared complication during mechanical thrombectomy (MT). We aimed to investigate the impact of procedural parameters and thrombus properties on the incidence of peripheral emboli after MT for large vessel occlusions (LVO). Methods: We performed a prospective analysis of patients with LVO stroke successfully treated with MT, defined as a score of 2b, 2c, or 3 on the thrombolysis in cerebral infarction (TICI) scale. A follow-up MRI including high-resolution diffusion-weighted imaging (DWI) was performed within 24 h following MT. The primary endpoint was the number and volume of peripheral emboli, classified as punctuate DWI lesions distant to the diffusion-restricted core lesion. Further analysis included the influence of baseline characteristics, procedural and outcome parameters, and thrombus properties on peripheral emboli. Results: Thirty-seven patients with successful MT met the inclusion criteria. Use of a balloon guide catheter (BGC) and TICI were the only independent predictors for a reduced number of peripheral emboli. The use of a BGC led to a significant reduction in the number and volume of peripheral emboli, with a median number/volume of peripheral emboli of 4.5/287 μl (IQR 1.25–8.25/76–569 μl) vs. 12/938 μl (IQR 4–19/242–1,836 μl). In cases where BGC was not employed, the number of peripheral emboli increased with decreasing TICI scores. Conclusions: BGC-aided MT reduces the number of peripheral emboli in successful but incomplete reperfusion (TICI 2b and 2c). The effectiveness of this strategy therefore goes above and beyond that which can be demonstrated by the TICI score alone.